2021
DOI: 10.1111/jcmm.16619
|View full text |Cite
|
Sign up to set email alerts
|

Systematic profiling of invasion‐related gene signature predicts prognostic features of lung adenocarcinoma

Abstract: Due to the high heterogeneity of lung adenocarcinoma (LUAD), molecular subtype based on gene expression profiles is of great significance for diagnosis and prognosis prediction in patients with LUAD. Invasion‐related genes were obtained from the CancerSEA database, and LUAD expression profiles were downloaded from The Cancer Genome Atlas. The ConsensusClusterPlus was used to obtain molecular subtypes based on invasion‐related genes. The limma software package was used to identify differentially expressed genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Furthermore, with the DEGs that overlapped with the PanCancer Immune Panel, the enriched GO categories indicated that the up-regulated DEGs were enriched in chemokines, B cell functions, and cytokine signaling in the immune system, and the down-regulated DEGs were enriched in interleukins, leukocyte functions, and NK cell functions. The overexpression of the genes in B cell functions in lung cancer has been reported [ 42 , 43 , 44 ]. Increased expression levels of BLK [ 42 ] and MS4A1 [ 43 ] have been reported in lung adenocarcinoma, and BLK and CD19 [ 44 ] have been reported to be significantly correlated with the overall survival in patients with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, with the DEGs that overlapped with the PanCancer Immune Panel, the enriched GO categories indicated that the up-regulated DEGs were enriched in chemokines, B cell functions, and cytokine signaling in the immune system, and the down-regulated DEGs were enriched in interleukins, leukocyte functions, and NK cell functions. The overexpression of the genes in B cell functions in lung cancer has been reported [ 42 , 43 , 44 ]. Increased expression levels of BLK [ 42 ] and MS4A1 [ 43 ] have been reported in lung adenocarcinoma, and BLK and CD19 [ 44 ] have been reported to be significantly correlated with the overall survival in patients with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of the genes in B cell functions in lung cancer has been reported [ 42 , 43 , 44 ]. Increased expression levels of BLK [ 42 ] and MS4A1 [ 43 ] have been reported in lung adenocarcinoma, and BLK and CD19 [ 44 ] have been reported to be significantly correlated with the overall survival in patients with lung adenocarcinoma. Some studies have reported decreased expressions of the genes in NK cell functions in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Univariate Cox regression analysis was performed to calculate the correlation between methylation level of CpG sites filtered in the above step and patient’s OS, and the p-value < 0.05 was considered in this study. Next, a Least Absolute Shrinkage and Selection Operator (LASSO) regression model was performed to screen the most useful prediction CpG sites, and a methylation-based classifier was constructed for predicting OS based on the sum of CpG site methylation levels weighted by the coefficients [ 12 ]. LASSO regression is a variable selection and shrinkage method for the regression models to identify the variables and relevant regression coefficients, which are established to minimize the prediction error.…”
Section: Methodsmentioning
confidence: 99%
“…Lung adenocarcinoma (LUAD) is the subtype of lung cancer with the highest prevalence [ 3 , 4 ]. Despite advancements in surgery, radiotherapy, chemotherapy, and other advanced therapeutics, the prognosis remains poor due to the high heterogeneity of LUAD [ 5 , 6 ]. As such, research into the molecular mechanisms and pathogenesis of LUAD requires further research to develop promising therapies.…”
Section: Introductionmentioning
confidence: 99%